Analysis of mangrove dynamics and its protection effect in the Guangdong-Hong Kong-Macao Coastal Area based on the Google Earth Engine platform - Zeng, Jiali; Ai, Bin; Jian, Zhuokai; Ye, Mingzhen; Zhao, Jun; Sun, Shaojie (Frontiers in Marine Science, 2023)
Mangroves are rapidly disappearing in several places of the world, and mangrove dynamics are becoming important evidence of ecological restoration and protection along the coast. Mangrove populations in the Guangdong-Hong Kong-Macao Coastal Area (GCA) have experienced a substantial impact of anthropogenic pressure in the 20th century. Monitoring its spatio-temporal variation and protection effect has been regarded as an important task in coastal management. In this study, we provided the comprehensive assessment of mangrove dynamics in the GCA and typical sites from 1988 to 2020 at eight-year intervals. At this time interval, mangrove ecosystems changed significantly as a result of global warming and human impacts. The geographical distribution of mangroves was obtained by applying the Random Forest (RF) classifier on Landsat images with a 30 m spatial resolution on the Google Earth Engine (GEE) platform, based on relevant indices such as Normalized Difference Mangrove Index (NDMI), Normalized Difference Vegetation Index (NDVI), Normalized Difference Suspended Sediment Index (NDSSI), Normalized Difference Built-up Index (NDBI) and Soil Adjusted Vegetation Index (SAVI). Quantitative evaluation indicated that overall accuracy of over 88% was achieved with RF classifier for mangrove extraction. In the GCA, mangrove area was 95.4 km2 in 1988, dropped to 71.4 km2 in 1996, then expanded to 127.5 km2 in 2020, with an overall dynamic rate of 1.02%. In typical sites, mangroves show a similar trend to the overall area. The subsequent mangrove growth is attributed to reserve establishment, accompanied by the expansion of replanted mangrove areas. In the GCA, provincial-level and county-level reserves show a high rate of mangrove dynamic, while national-level reserves display a low rate of mangrove dynamic. The dynamic rate in reserves of the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) is higher than other parts of the GCA, indicating that the effect of mangrove protection is better in the GBA. The results of this study will provide scientific foundations for the sustainable management and conservation of mangrove ecosystem, the quantification of ecosystem services (such as coastal protection and carbon storage), as well as the formulation of strategies for mitigating and adapting to climate change.